One Decade of Social Forestry Research in Indonesia (2015–2025): A Bibliometric Analysis - Suryaningsih; Susiyanti Meilina; Berian Hariadi; Rianda Prima Putri (Jurnal Administrasi Publik dan Pemerintahan, 2026)
Social forestry in Indonesia has gained increasing scholarly attention as a governance approach for reconciling forest conservation with community rights, livelihood improvement, and sustainable rural development. This study maps the evolution of Indonesian social forestry research and examines how a national priority program aligns with scholarly trends through a bibliometric approach. Using a PRISMA-informed workflow, we identified and screened records and analyzed 176 Scopus-indexed journal articles (2015–2025) with Bibliometrix/Biblioshiny and VOSviewer. We assessed annual scientific production, leading contributors (authors, institutions, and countries), collaboration structures, and thematic development via co-occurrence networks, three-field plots, and thematic mapping. Results show strong publication growth, accelerating in the late 2010s and peaking in the early 2020s. Knowledge production is highly concentrated in Indonesia (402 country contributions; 75.14%), with selective international engagement from Australia, Japan, the United States, and the United Kingdom. Core contributors include Maryudi A (16) and Sahide MAK (14), while leading affiliations cluster in Indonesian universities, particularly IPB University, Universitas Gadjah Mada, and Hasanuddin University. The thematic core centers on Indonesia–social forestry–forest management and community forestry, supported by strands on agroforestry, sustainability, governance, policy implementation, and livelihoods. Collaboration is substantial (mean 4.74 co-authors/document; 33.52% international co-authorship). Key gaps include limited integration of politico-bureaucratic and Indigenous dimensions, weak conceptual bridging from place-based land-use studies, and underdeveloped links to climate–carbon and commodity-livelihood agendas. Limitations include Scopus-only coverage.